PRESTASI SENI TARI SDN TANJUNGSARI I KECAMATAN TANJUNGSARI (Penelitian Studi Kasus di SDN Tanjungsari I Kecamatan Tanjungsari Kabupaten Sumedang) - Fatimah, Fatmah Hafsari; Julia, Julia; Sunaengsih, Cucun (Jurnal Pena Ilmiah, 2017)
The researchers choose SDN Tanjungsari I due to results of a survey of Sumedang District Education Office stating that SDN Tanjungsari I as a school with a good performance in the field of dance. This study uses qualitative research with case study design that aims to know more about the art of dance achievement in SDN Tanjungsari I. In a case study, the researcher is the main instrument. While data collection techniques in this study were interviews, observation, documentation and recording. Research results revealed that: (1) the achievement of dance SDN Tanjungsari I spelled out very much because every year is sure to be a champion in the activities FLS2N (National Student Competition Festival); (2) The main factors supporting the achievement of dance SDN acquisition Tanjungsari I which student talent, presence and expertise studio dance coach, parent support, and motivation; and (3) the process of learning to dance in SDN Tanjungsari I carried out systematically and conducive.